Nineteen proposals to curb abuse in antidumping and countervailing duty proceedings - Campos, Aluisio de Lima (Revista do IBRAC, 2025)
This is the third article of a series designed to show the serious problems related to antidumping (AD) and anti-subsidy (AS) (also known as countervailing duty – CVD) procedures and propose solutions. In the first article,1 published in 1995, I analyzed the changes introduced by the Uruguay Round Agreements Act (URAA), the U.S. law that implemented the agreements reached in the Uruguay Round of multilateral trade negotiations, and pointed out where the inconsistencies of the law were in a comparison with the then new World Trade Organization (WTO) instruments for AD and AS procedures.